NCT life variety show as a persuasive media for Korean tourism promotion: Peirce’s semiotic observation - Arba Monita Budiani; Rudi Adi Nugroho (Journal of Korean Applied Linguistics, 2023)
This research discussed signs in terms of icons, indexes, and symbols on the variety show named NCT Life: Hot and Young Seoul Trip using the semiotic theory of Charles Sanders Peirce. The purpose of this research is to describe icons, indexes, and symbols related to tourism and interpret these signs with contextual meaning. The reason for doing this research is to look for signs that refer to persuasive tourism promotion activities contained in the variety show. This research employed the descriptive qualitative design with the findings on each icon, index, symbol, and contextual meaning presented in the form of a description. The results of this study indicate that there are categories of icons, indexes, and symbols related to tourism promotion in Seoul, South Korea. Icon has three categories related to brand ambassadors, tourist attractions, and tourist activities. The index has four categories related to the background illustration for NCT members introduction, expressions of feelings, figurative expressions, and gestures. The symbol has three categories related to logos, slogans, and additional information related to activities and tourist attractions. Then, the contextual meaning of the signs found leads to several contexts, all of which also refer to tourism promotion activities delivered through the media of variety shows. On this basis, the research suggests that there is tourism promotion packaged in events through variety shows carried out by NCT members as performers by visiting or trying various tourist activities around Seoul and recommending them to the audience.